Multiple urolithiases in pediatric acute lymphoblastic leukemia - Fujishiro, Ayumi; Matsuno, Ryosuke; Omachi, Taichi; Yamazoe, Takashi; Okano, Mai; Kaneko, Kazunari (Indian Journal of Child Health, 2021)
Current study is a case report of a 5-year-old patient with T-cell acute lymphoblastic leukemia (ALL) and multiple urolithiasis. Complex factors, including glucocorticoid-induced hypercalciuria, fluid restriction for the syndrome of inappropriate secretion of antidiuretic hormone, and long-term bed rest, predispose children with ALL to develop urolithiasis. To prevent urinary urolithiasis formation, urinary calcium excretion should be monitored during chemotherapy and when administering glucocorticoids.